Effects of the Brown Seaweed Laminaria japonica Supplementation on Serum Concentrations of IgG, Triglycerides, and Cholesterol, and Intestinal Microbiota Composition in Rats - Kim, Jae-Young; Kwon, Young Min; Kim, In-Sung; Kim, Jeong-A.; Yu, Da-Yoon; Adhikari, Bishnu; Lee, Sang-Suk; Choi, In-Soon; Cho, Kwang-Keun (Frontiers in Nutrition, 2018)
The intestinal microbial communities play critical roles in various aspects of body function of the host. Prebiotics, such as dietary fiber, can affect health of the host by altering the composition of intestinal microbiota. Although brown seaweed Laminaria japonica (L. japonica) is rich in dietary fiber, studies on its prebiotic potential are quite rare. In the present study, basal diet supplemented with dried L. japonica (DLJ), heated dried L. japonica (HLJ), or heated dried L. japonica with added fructooligosaccharide (FHLJ) was fed to rats for 16 weeks. Serum concentrations of IgG, triglyceride, and cholesterol were measured. In addition, the intestinal microbiota composition was analyzed by high-throughput sequencing of 16S rRNA gene. As compared to the control group, DLJ, HLJ and FHLJ groups showed significantly higher serum IgG concentration, but had lower weight gain and serum triglyceride concentration. In addition, DLJ, HLJ and FHLJ groups showed lower Fimicutes to Bacteroidetes ratio as compared to the control group. As compared to the control group, obesity-associated bacterial genera (Allobaculum, Turicibacter, Coprobacillus, Mollicute, and Oscilibacter), and the genera with pathogenic potentials (Mollicute, Bacteroides, Clostridium, Escherichia, and Prevotella) were decreased while leanness-associated genera (Alistipes, Bacteroides, and Prevotella), and lactic acid bacterial (LAB) genera (Subdoligranulum, Streptococcus, Lactobacillus, Enterococcus, and Bifidobacterium) were increased in all treatment groups. On the contrary, butyric acid producing genera including Subdoligranulum, Roseburia, Eubacterium, Butyrivibrio, and Anaerotruncus increased significantly only in FHLJ group. The results support multiple prebiotic effects of seaweed L. japonica on rats as determined by body weight reduction, enhanced immune response, and desirable changes in intestinal microbiota composition, and suggest the great potential of L. japonica as an effective prebiotic for promotion of host metabolism and reduction of obesity in humans.